Reflecting about international law system using bilateral investment treaties - Mosquera Monelos, Susana (Revista Tribuna Internacional, 2017)
The necessary review of some key concepts to adapt international law to its new circumstances seems quite urgent, especially concerning the international personhood concept. Identify the owner of the international obligation to enforce the application of the international law demanding this owner responsibility, is a main question in the precise moment when the international sources of law appears everywhere. For such a reason revisiting some main concepts, as sources of law and subject, becomes relevant to be able to answer the question if, some of the new non-state actors could be granted with full international personhood. Considering the position of corporations as subject, and trade business agreements as sources of law this paper will try to offer a new focus approach to some of the main concepts of international law with the purpose to reinforce the relationship between international and domestic law.